2021
DOI: 10.3389/fphar.2021.757666
|View full text |Cite|
|
Sign up to set email alerts
|

Antiviral and Immunomodulatory Effects of Pelargonium sidoides DC. Root Extract EPs® 7630 in SARS-CoV-2-Infected Human Lung Cells

Abstract: Treatment options for COVID-19 are currently limited. Drugs reducing both viral loads and SARS-CoV-2-induced inflammatory responses would be ideal candidates for COVID-19 therapeutics. Previous in vitro and clinical studies suggest that the proprietary Pelargonium sidoides DC. root extract EPs 7630 has antiviral and immunomodulatory properties, limiting symptom severity and disease duration of infections with several upper respiratory viruses. Here we assessed if EPs 7630 affects SARS-CoV-2 propagation and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 110 publications
1
31
1
2
Order By: Relevance
“…Root Extract EPs 7630 has an ability to reduce virus-induced immune response in human lung cells. The study showed that CXCL10 and other pro-inflammatory cytokines (e.g., CXCL9, IL-8, IL-13, TNF-α) were reduced as the result of EPs 7630 [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Root Extract EPs 7630 has an ability to reduce virus-induced immune response in human lung cells. The study showed that CXCL10 and other pro-inflammatory cytokines (e.g., CXCL9, IL-8, IL-13, TNF-α) were reduced as the result of EPs 7630 [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20]. Использование Умкалора в клинической практике обусловливают следующие доказанные эффекты препарата: антимикробный (антивирусный, антибактериальный, антимикотический и антипротозойный) [21][22][23][24][25], иммуномодулирующий [21,26,27], противовоспалительный [28], улучшение дренажной функции ВДП (муколитический, секретомоторный) [27].…”
Section: Bronchopulmonology Otorhinolaryngologyunclassified
“…Ein bereits in vielen vor- wie klinischen Studien sowie kommerziell genutzter Extrakt aus Pelargonium sidoides (EPs ® 7630) wird bezüglich seiner Fähigkeit zur Virushemmung ausschließlich von SARS-CoV-2 im heute üblichen Ansatz mit VeroFM- sowie zusätzlich in einem mit Calu-3-Zellen untersucht 21 . Calu-3 (aus cancer of the lung) ist eine 1976 eingeführte, ebenfalls sehr gebräuchliche menschliche Lungen-Adenokarzinom-Zelllinie mit voll erhaltener Interferonkompetenz, die eigentlich der Testung von Krebsmedikamenten dient.…”
Section: Grundlagenforschungunclassified